Deciphering Key Foreign Body Reaction-Related Transcription Factors and Genes Through Transcriptome Analysis - Liu, Wei; Xiong, Shaoheng; Du, Jing; Song, Yajuan; Wang, Tong; Zhang, Yu; Dong, Chen; Huang, ZhaoSong; He, Qiang; Yu, Zhou; Ma, Xianjie (Frontiers in Molecular Biosciences, 2022)
Background: Silicone implants are widely used in the field of plastic surgery for wound repair and cosmetic augmentation. However, molecular mechanisms and signaling pathways underlying the foreign body reaction (FBR) of a host tissue to the silicone require further elucidation. The purpose of this study was to identify key FBR-related transcription factors (TFs) and genes through transcriptome analysis. Methods: We used a rat model with a subcutaneous silicone implant in the scalp and performed high throughput sequencing to determine the transcriptional profiles involved in the FBR. The function was analyzed by Gene Ontology (GO) and the Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway-enrichment analysis. A protein-protein interaction (PPI) network of differentially expressed mRNAs (DEmRNAs) was constructed to identify the hub genes and key modules and to determine the regulatory TF-mRNA relationships. In addition, the hub gene and transcript expression levels were determined by Quantitative Reverse Transcription Polymerase Chain Reaction (qRT-PCR). Myofibroblasts differentiation and macrophage recruitment were identified by immunofluorescence. The protein expression of MMP9 was detected by immunohistochemistry and Western blot. Results: We identified ten hub genes (Fos, Spp1, Fn1, Ctgf, Tlr2, Itgb2, Itgax, Ccl2, Mmp9, and Serpine1) and three TFs (FOS, IRF4, and SPI1) that may be crucial (particularly FOS) for the FBR. Furthermore, we identified multiple differentially expressed genes involved in several important biological processes, including leukocyte migration, cytokine‒ cytokine receptor interaction, phagocytosis, extracellular matrix (ECM) organization, and angiogenesis. We also identified potentially significant signaling pathways, including cytokine‒cytokine receptor interaction, phagosome, ECM‒receptor interaction, complement and coagulation cascades, the IL-17 signaling pathway, and the PI3K‒Akt signaling pathway. In addition, qRT-PCR confirmed the expression patterns of the TFs and hub genes, Western blot and immunohistochemistry validated the expression patterns of MMP9. Conclusions: We generated a comprehensive overview of the gene networks underlying the FBR evoked by silicone implants. Moreover, we identified specific molecular and signaling pathways that may perform key functions in the silicone implant-induced FBR. Our results provide significant insights into the molecular mechanisms underlying silicone-induced FBR and determine novel therapeutic targets to reduce complications related to silicone implantation.